Exploring Iḥtikār (Hoarding) and Fraud in Football Ticketing: An Islamic Criminal Law Review - Muhammad Faiz Abdullah; Ramadani (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study investigates the growing phenomenon of ticket hoarding (Iḥtikār) and counterfeiting in Indonesian football matches, which causes significant harm to both consumers and event organizers. The purpose of this research is to analyse these practices from the perspectives of Islamic criminal law and Indonesian positive law, and to evaluate the legal sanctions applicable to such offenses. Employing a juridical-empirical method with a qualitative approach, data were collected through interviews, observation, and documentation, focusing on cases at Baharoeddin Siregar Stadium, Lubuk Pakam, North Sumatra. The findings reveal that ticket hoarding and forgery constitute jarīmah taʿzīr and iḥtikār in Islamic criminal law, due to elements of fraud, injustice, and public harm. Under Indonesian law, these acts violate provisions on trade monopolies and meet the criteria for fraud and forgery as defined in the Criminal Code (KUHP) and Law No. 7 of 2014. This research offers an original contribution by contextualizing Islamic criminal law in economic crime, highlighting the need for policy reform and stronger enforcement to combat illegal ticketing practices.